Implementasi metode Karyawisata Sekolah Dasar - M. Nurois Amin (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2020)
Elementary school age children are a period of play and activity for students and need movement in learning activities and interact directly with what is being learned. In reality, many learning activities in elementary schools still use the teacher center approach, namely the teacher as a source of knowledge. In the learning process, teachers in conveying learning competencies in the classroom using the lecture method and have not optimally utilized the surrounding environment in learning. The use of methods that are too frequent and the place of learning that is always in the class makes students bored in participating in learning. In the early learning activities the students looked enthusiastic, but a few minutes after entering the core lesson the students seemed to be playing alone due to boredom, as a result the student's learning achievement was not optimal. The problems above are classical problems that occur in every elementary school